Bone density of women who have recovered from anorexia nervosa - Hartman, David; Crisp, Arthur; Rooney, Barbara; Rackow, Chloe; Atkinson, Richard; Patel, Sanjeev (The International journal of eating disorders, 2000)
Objective To examine bone density in 19 women who had previously experienced classical anorexia nervosa from which they had been fully recovered for a mean of 21 years (current characteristics: median age 40.2 years; Eating Attitudes Test [EAT] score 2; body mass index [BMI] 21.1; average 1.8 offspring). Method Probands were compared, blindly, in respect of bone density, with 13 control subjects matched for age and sex and with no history of eating disorders. Dual energy X‐ray absorptiometry (DXA) was used to evaluate the bone mineral density (BMD) of the lumbar spine and the head of the femur. Results Femur BMD was still significantly less among ex‐anorectic sufferers. Two subjects had experienced pathological fractures while anorectic, both having been strenuous exercisers. None appeared to have suffered post illness fractures. BMD at follow‐up did not relate to the severity or chronicity of previous anorexia nervosa. Discussion Full clinical recovery from anorexia nervosa does not quite confer full establishment of normal bone density. However, pathological fractures are not a feature thereafter, within middle life. © 2000 John Wiley & Sons, Inc. Int J Eat Disord 28: 107–112, 2000.